Statistical Validation of 2% Lignosulfonate as a Sustainable Stabilizer for Expansive Clay - Rivianto, Arif; Candra, Agata Iwan; Nursandah, Fauzie; Mustofa, Imam (Kadiri University, 2025)
Expansive clay soils undergo volumetric changes due to fluctuations in moisture content, which can cause structural damage to foundations, pavements, and embankments. Traditional stabilization methods, such as cement and lime, are effective but have a significant environmental impact, highlighting the need for more environmentally friendly alternatives. Lignosulfonate (LS), an organic stabilizer derived from industrial by-products, offers a more sustainable approach to improving soil strength and stability. This study evaluates the effect of 2% lignosulfonate on the unconfined compressive strength (UCS) of expansive clays. The research method involved mixing LS at 2% of the dry weight of the soil into the expansive clay (CL-ML) and conducting UCS tests on three untreated (control) samples and six treated samples. Statistical analysis was used to assess the significance of the differences between the two groups. Results show that the UCS increased from 236.29 kPa in the control group to 291.49 kPa in the treated group, reflecting a 23.37% improvement. Poisson's ratio decreased from 0.300 to 0.200, indicating reduced lateral deformation and enhanced soil stiffness, which improves the bearing capacity and stability of structures built on it. The UCS values ​​were observed to be consistent supported by low standard deviation. The study highlights the critical role of adequate sample replication and control over operational variables such as moisture content, compaction, and LS dispersion to ensure reliable and reproducible stabilization outcomes. This study strengthens the empirical basis for the application of LS as a sustainable and environmentally friendly stabilizer for expansive clays.